Immature Dendritic Cell Therapy Confers Durable Immune Modulation in an Antigen-Dependent and Antigen-Independent Manner in Nonobese Diabetic Mice - Jeannette Lo; Chang-Qing Xia; Ruihua Peng; Michael J. Clare-Salzler (Journal of Immunology Research)
Dendritic cell (DC) immunotherapy has been effective for prevention of type 1 diabetes (T1D) in NOD mice but fails to protect if initiated after active autoimmunity. As autoreactivity expands inter- and intramolecularly during disease progression, we investigated whether DCs unpulsed or pulsed with β cell antigenic dominant determinants (DD), subdominant determinants (SD), and ignored determinants (ID) could prevent T1D in mice with advanced insulitis. We found that diabetes was significantly delayed by DC therapy. Of interest, DCs pulsed with SD or ID appeared to provide better protection. T lymphocytes from DC-treated mice acquired spontaneous proliferating capability during in vitro culture, which could be largely eliminated by IL-2 neutralizing antibodies. This trend maintained even 29 weeks after discontinuing DC therapy and appeared antigen-independent. Furthermore, CD4+Foxp3+ T regulatory cells (Tregs) from DC-treated mice proliferated more actively in vitro compared to the controls, and Tregs from DC-treated mice showed significantly enhanced immunosuppressive activities in contrast to those from the controls. Our study demonstrates that DC therapy leads to long-lasting immunomodulatory effects in an antigen-dependent and antigen-independent manner and provides evidence for peptide-based intervention during a clinically relevant window to guide DC-based immunotherapy for autoimmune diabetes.